ANALISIS FAKTOR RISIKO TERHADAP KEJADIAN SINDROM SYOK DENGUE (SSD) PADA ANAK DI RSUD DR SOEKARDJO KOTA TASIKMALAYA TAHUN 2020-2022 - Rida Sophiatul Khofifah (2023)
The large number of cases of dengue shock syndrome () in children, so the need for early diagnosis by knowing the risk factors that affect SSD. This study aims to analyze several risk factors for the occurrence of SSD and find out the most dominant risk factors for the occurrence of SSD in children. This study used a cross-sectional observational analytic method, using medical record data for 2020-2022. The research sample was pediatric patients aged 0-18 who fit the inclusion and exclusion criteria. SSD risk factors were analyzed by chi square test, and logistic regression. From this study, 124 respondents were obtained, consisting of 70 cases of SSD and 54 cases of DHF. The chi square test showed that the variables were age ≤ 5 years (P=0.001), nutritional status (P=0.058), gender (P=0.916), referral (P=0.021), length of fever ≥ 4 days before being hospitalized (P=0.002 ), leukocytes > 5000 (P=0.032), platelets < 100000 (P=0.010), and hemoconcentration (P=0.000). Logistic regression analysis found that the most dominant factor in the occurrence of SSD is hemoconcentration (OR : 31.139). The conclusion of this study is that age, referral, duration of fever before being treated, leukocyte levels, platelet levels, and hemoconcentration have a significant relationship, while nutritional status and gender do not have a significant relationship with the incidence of SSD. The most dominant risk factor for SSD is hemoconcentration.